2022
DOI: 10.1136/bmjopen-2022-062979
|View full text |Cite
|
Sign up to set email alerts
|

Understanding the biology, morbidity and social contexts of adolescent tuberculosis: a prospective observational cohort study protocol (Teen TB)

Abstract: IntroductionA considerable burden of the tuberculosis (TB) epidemic is found in adolescents. The reasons for increased susceptibility to TB infection and higher incidence of TB disease in adolescence, compared with the 5–10 years old age group, are incompletely understood. Despite the pressing clinical and public health need to better understand and address adolescent TB, research in this field remains limited.Methods and analysisTeen TB is an ongoing prospective observational cohort study that aims to better … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 8 publications
(2 citation statements)
references
References 28 publications
0
2
0
Order By: Relevance
“…Previous studies have shown a higher burden of MTB infection among the elderly [ 31 ] and an association between unsuccessful treatment and increasing age [ 32 ]. Children and adolescents have reduced resistance to TB infection, coupled with increased opportunities for cross infection in collective life, making them also a high-risk group for TB [ 33 , 34 ]. From a sociological perspective, middle-aged individuals, being crucial for social development, typically exhibit better health awareness and are more efficient in implementing health policies.…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies have shown a higher burden of MTB infection among the elderly [ 31 ] and an association between unsuccessful treatment and increasing age [ 32 ]. Children and adolescents have reduced resistance to TB infection, coupled with increased opportunities for cross infection in collective life, making them also a high-risk group for TB [ 33 , 34 ]. From a sociological perspective, middle-aged individuals, being crucial for social development, typically exhibit better health awareness and are more efficient in implementing health policies.…”
Section: Discussionmentioning
confidence: 99%
“…As case patients and controls in Teen TB were unmatched, regression modelling was also used to address confounding and adjust for imbalances between the study groups in our study. A detailed description of the Teen TB study methods and procedures can be found elsewhere [ 15 ].…”
Section: Methodsmentioning
confidence: 99%